Determination of water-soluble forms of oxalic and formic acids in soils by ion chromatography; IOP Conference Series: Earth and Environmental Science; Vol. 33 : Contemporary Issues of Hydrogeology, Engineering Geology and Hydrogeoecology in Eurasia - Karicheva E. Yu. Ekaterina Yurievna (Hydrogeochemistry, 2016)
Title screen